2013
DOI: 10.1021/co300119q
|View full text |Cite
|
Sign up to set email alerts
|

Combinatorial Approach to Improve Photoelectrodes Based on BiVO4

Abstract: The photoelectrochemical behavior of materials based on binary Bi-V oxides was investigated by preparing libraries of ternary metal oxides using high-throughput combinatorial inkjet printing of oxide precursors onto conductive glass substrates. Subsequent pyrolysis of the printed films, with addition of various levels of a third metal oxide precursor, produced libraries of metal oxides that were immersed under potential control into an electrolyte solution and evaluated for water photooxidation or photoreducti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
42
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(43 citation statements)
references
References 44 publications
1
42
0
Order By: Relevance
“…Supported by computation, a primary conclusion drawn from this work is that Mo and W alloying, separately and together, serve as shallow electron donors. Later work by Jiang et al 14 used ink jet printing to produce discrete composition arrays to compare the effect of alloying each of W, Mo, Mn, Co, Cr, Mg, Fe, Cu. Measurements in 0.1 K2SO4 revealed that the best PEC performance is obtained with W alloying.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Supported by computation, a primary conclusion drawn from this work is that Mo and W alloying, separately and together, serve as shallow electron donors. Later work by Jiang et al 14 used ink jet printing to produce discrete composition arrays to compare the effect of alloying each of W, Mo, Mn, Co, Cr, Mg, Fe, Cu. Measurements in 0.1 K2SO4 revealed that the best PEC performance is obtained with W alloying.…”
Section: Introductionmentioning
confidence: 99%
“…12 Doping, or low level alloying of three, four, or more additional metals into m-BiVO4 is an active area of research, with particularly notable performance enhancements achieved by inclusion of Mo, W, and select rare earth elements, alone and in combination. [13][14][15][16][17][18][19] The underlying origin of the observed performance improvement remains an active area of investigation, with spectroscopic studies indicating a decrease in electron trap state concentration producing an increase in electron and hole mobilities 10 and/or increased charge carrier concentration induced by electron donating elements, in particular W and Mo. 20 Changes in the band gap and movement of band edges have also been reported.…”
mentioning
confidence: 99%
“…Reducing the band gap of BVO to 1.8-2.2 eV via alloying, doping, strain, or other types of band gap engineering is thus an important goal for making practical water splitting devices based on this material. [10][11][12][13] Although its non-optimal band gap restricts its ultimate efficiency, poor charge transport is the more immediate limitation on the photoelectrochemical performance of BVO. BVO is reported to have relatively short diffusion lengths both for holes [14][15][16][17] (which motivates the design of nanostructured films to achieve efficient hole collection) and electrons [18][19][20] (which forces the use of optically thin films for efficient electron collection).…”
Section: Introductionmentioning
confidence: 99%
“…Such inkjet printed materials could be metal oxides as recently reviewed by Liu et al [25] Parkinson and co-workers formulated inks that contain mainly metal nitrates that were thermally converted into oxides at 500°C. [26][27][28][29][30] Several multi metal oxide patterns were created to find very active photoelectrocatalysts for water splitting, such as Bi−V−W-based oxides with specific stoichiometric composition. [29] The concept of pyrolyzing metal nitrates has also been employed by Katz et al who optimized the solubility of some metal salts by adjusting the pH of the aqueous ink solutions to acidic or neutral, respectively.…”
Section: Inkjet Printing Of Electrocatalystsmentioning
confidence: 99%
“…[26][27][28][29][30] Several multi metal oxide patterns were created to find very active photoelectrocatalysts for water splitting, such as Bi−V−W-based oxides with specific stoichiometric composition. [29] The concept of pyrolyzing metal nitrates has also been employed by Katz et al who optimized the solubility of some metal salts by adjusting the pH of the aqueous ink solutions to acidic or neutral, respectively. [31] The potential of the high-throughput multi-component deposition by inkjet printing has been demonstrated by Liu et al [32] Several metal salts based on nitrate, chloride, acetate, alkoxide and silicate were applied in parallel using colloidal nanoparticle dispersions in amphoteric non-aqueous solvents (Fig.…”
Section: Inkjet Printing Of Electrocatalystsmentioning
confidence: 99%